Compatible and Incompatible Mycorrhizal Fungi With Seeds of Dendrobium Species: The Colonization Process and Effects of Coculture on Germination and Seedling Development - Ma, Guang-Hui; Chen, Xiang-Gui; Selosse, Marc-André; Gao, Jiang-Yun (Frontiers in Plant Science, 2022)
Orchids highly rely on mycorrhizal fungi for seed germination, and compatible fungi could effectively promote seeds germinated up to seedlings, while incompatible fungi may stimulate germination, but not support subsequent seedling development. In this study, we compared the fungal colonization process among two compatible and two incompatible fungi during seed germination of Dendrobium officinale. The two compatible fungi, Tulasnella SSCDO-5 and Sebacinales LQ, originally from different habitats, could persistently colonize seeds and form a large number of pelotons continuously in the basal cells, and both fungi promoted seed germination up to seedling with relative effectiveness. In contrary, the two incompatible fungi, Tulasnella FDd1 and Tulasnella AgP-1, could not persistently colonize seeds. No pelotons in the FDd1 treatment and only a few pelotons in the AgP-1 treatment were observed, moreover, no seedlings were developed at 120 days after incubation in either incompatible fungal treatment. The pattern of fungal hyphae colonizing seeds was well matched with the morphological differentiation of seed germination and seedling development. In the fungal coculture experiments, for both orchids of Dendrobium officinale and D. devonianum, cocultures had slightly negative effects on seed germination, protocorm formation, and seedling formation compared with the monocultures with compatible fungus. These results provide us with a better understanding of orchid mycorrhizal interactions, therefore, for orchid conservation based on symbiotic seed germination, it is recommended that a single, compatible and ecological/habitat-specific fungus be utilized for seed germination.